The Arabidopsis pi4kIIIβ1β2 double mutant is salicylic acid-overaccumulating: a new example of salicylic acid influence on plant stature - Janda, Martin; Šašek, Vladimír; Ruelland, Eric (Plant signaling & behavior, 2014)
Growth is the best visible sign of plant comfort. If plants are under stress, a difference in growth with control conditions can indicate that something is going wrong (or better). Phytohormones such as auxin, cytokinins, brassinosteroids or giberellins, are important growth regulators and their role in plant growth was extensively studied. On the other hand the role of salicylic acid (SA), a phytohormone commonly connected with plant defense responses, in plant growth is under-rated. However, studies with SA-overaccumulating mutants directly showed an influence of SA on plant growth. Recently we characterized an Arabidopsis SA-overaccumulating mutant impaired in phosphatidylinositol-4-kinases (pi4kIIIβ1β2). This mutant is dwarf. The crossing with mutants impaired in SA signaling revealed that pi4kIIIβ1β2 stunted rosette is due to high SA, while the short root length is not. This brings into evidence that upper and lower parts of the plants, even though they may share common phenotypes, are differently regulated.
Keywords: Salicylic Acid; Plant Leaves; salicylic acid; Arabidopsis; mutace; proteiny huseníčku; plant growth; kyselina salicylová; Mutation; Arabidopsis Proteins; kořeny rostlin; 1-fosfatidylinositol-4-kinasa; 1-Phosphatidylinositol 4-Kinase; Plant Roots; phosphatidylinositol-4-kinase; signaling; listy rostlin